Intelligent Information Processing VI 7th IFIP TC 12 International Conference, IIP 2012, Guilin, China, October 12-15, 2012, Proceedings - Shi, Zhongzhi; Leake, David; Vadera, Sunil (IFIP Advances in Information and Communication Technology,, 2012)
This book constitutes the refereed proceedings of the 7th IFIP TC 12 International Conference on Intelligent Information Processing, IIP 2012, held in Guilin, China, in October 2012. The 39 revised papers presented together with 5 short papers were carefully reviewed and selected from more than 70 submissions. They are organized in topical sections on machine learning, data mining, automatic reasoning, semantic web, information retrieval, knowledge representation, social networks, trust software, internet of things, image processing, and pattern recognition.